Selection of performance indicators for the system of bench tests of unmanned aerial vehicles - M. A. Kovalev; A. V. Kirillov; V. V. Sitnikov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
The issues of evaluating the effectiveness of the process of bench testing of unmanned aerial vehicles are considered. It is noted that the effectiveness of the tests can be assessed using four main indicators: economic efficiency, test duration, test reliability, and measurement accuracy. Mathematical expressions are proposed to determine the numerical value of each indicator. The issues of assessing the cost-effectiveness of testing unmanned aerial vehicles conducted at different stages of the product life cycle are considered. A methodology for evaluating the effectiveness of conducting ground tests based on multi-criteria analysis mechanisms is proposed. An example of calculating a generalized indicator of the effectiveness of testing the power supply system of an aircraft-type unmanned aerial vehicle when on-board electric power generators are operating under different loads is given.